Improved Global Maximum Power Point Tracking Technique for a Partially Shaded Solar Photovoltaic Array Using Capacitor Transient Effect - Sakthivel, Senthamizh Selvan; Arunachalam, Venkadesan; P, Saravana Prakash; K, Sedhuraman (IEEE transactions on industrial informatics, 2024)
This article focuses on the global maximum power point (GMPP) tracking by a unique P-V curve tracing approach, for a partially shaded condition of a solar photovoltaic (PV) array. The technique utilizes the capacitor transient phenomena for obtaining the P-V curve, by which GMPP is tracked. Although existing maximum power point tracking (MPPT) techniques/algorithms works on the P-V curve tracing, it possess certain disadvantages, such as dependence on the solar PV array/module parameters, considerable settling time and complex algorithms. However, the technique proposed tracks the GMPP with less tracking time of 0.189 s and has minimal oscillations before convergence with tracking efficiency of 99%. In addition, the technique demands only one additional switch across the solar PV array terminals and independent of the converter and solar PV array/module parameters. The proposed technique is validated by extensive simulations and verified in a real-time hardware setup of 300 W solar PV array.